Pemanfaatan Model Pembelajaran Projek berbantuan Animasi pada Siswa SD - Nita Hidayati; Lessa Roesdiana (IKIP PGRI Bojonegoro, 2021)
ABSTRACTThe curriculum has an important role in the learning process. In the classroom, knowledge must be understood not only by the teacher but also by all students. Here's where teacher-student collaboration comes into play. Students' potential must be developed through the use of an innovative and constructive learning strategy that will improve students' capacity to understand the subject matter. One way to make it happen is by applying a learning model that is in accordance with the new paradigm of education, learning that can increase student activity in the learning process and maximize the interaction between learning components. One alternative to optimize the learning process is the Project Based Learning model. Students will understand better if the teacher in learning uses concrete objects/animations that resemble the actual atmosphere. To support the implementation of the Project Based Learning model, one of the media that can be used is animation media. Based on these problems, we intend to organize the preparation of animated learning media in a project-based learning model for elementary school students. The method used is the method of approach and method of implementation. The output targets of this activity are: increasing the mastery and skills of teachers in the preparation of learning media. The result of this activity is there are addition of new knowledge for teachers in the preparation of learning media, which with this knowledge can facilitate students in learning mathematics. Keywords: Animation Learning Media, Project Based Learning Model, Mathematics Learning Outcomes ABSTRAKKurikulum memegang peranan penting dalam proses pembelajaran. Di dalam kelas, pengetahuan harus dipahami tidak lagi hanya pada guru tetapi juga pada semua siswa. Di sinilah kolaborasi antara guru dan siswa masuk. Potensi siswa harus dikembangan melalui penerapan model pembelajaran inovatif dan konstruktif yang nantinya akan dapat meningkatkan kemampuan siswa dalam memahami materi pelajaran. Salah satu cara untuk mewujudkannya dengan menerapkan model pembelajaran yang sesuai dengan paradigma baru pendidikan, pembelajaran yang dapat meningkatkan keaktifan siswa dalam proses pembelajaran dan memaksimalkan interaksi antara komponen pembelajaran. Salah satu alternatif untuk mengoptimalkan proses pembelajaran, yakni model Project Based Learning. Siswa akan lebih mengerti dan paham jika guru dalam pembelajaran menggunakan benda konkret/animasi menyerupai suasana sebenarnya. Untuk mendukung penerapan model Project Based Learning maka salah satu media yang dapat digunakan adalah media animasi. Atas dasar permasalahan tersebut kami bermaksud akan mengadakan penyusunan media pembelajaran animasi dalam model pembelajaran berbasis projek bagi SD. Metode yang digunakan adalah metode pendekatan dan metode pelaksanaan. Target luaran kegiatan ini menambah penguasaan dan keterampilan guru dalam penyusunan media pembelajaran. Hasil dari pelatihan ini adalah adanya penambahan pengetahuan baru bagi guru dalam penyusunan media pembelajaran, yang mana dengan pengetahuan ini dapat mempermudah siswa dalam pembelajaran matematika. Kata Kunci: Media Pembelajaran Animasi, Model Pembelajaran Berbasis Projek, Hasil Belajar Matematika